CHALLENGES FOR INTERACTION DESIGN EDUCATION IN THE SOUTH: A CASE STUDY OF BOTSWANA. (29th January 2020) - Lotz, Nicole; Sharp, Helen
Abstract: In a long‐term partnership between a university in the UK and one in Botswana teaching interaction design, the Botswana cohort of students consistently performed less well than their UK counterparts. To investigate this, we conducted a pair of design protocol studies: one in the UK and one in Botswana. Our findings show that designer behaviour differs in the two contexts in terms of process, use of ideation techniques and solution and problem focus, when approaching the task. More specifically, UK students follow the approach taught in the module, while this process conflicts with Botswana students' behaviours. However, we also find that Botswana students prioritise the external context of the designed product rather than its interaction characteristics, which is problematic as interaction is the key feature of interactive products. These results are significant because without leveraging indigenous knowledge to design interaction that supports local user characteristics and context, sustainable and equitable development through technological innovation will be suppressed. In this paper, we highlight challenges for interaction design education in Botswana, which include how to recognise and support a diversity of design approaches while providing suitable pedagogic scaffolding. © 2020 John Wiley & Sons, Ltd.